Application and Optimization in Chromium-Contaminated Wastewater Treatment of the Reverse Osmosis Technology - A Ameri; M Gholami; F Vaezi; M Rahimi; M Mahmodi; B Moosavi (Tehran University of Medical Sciences, 2008)
Background: Chromium (Cr) is the most important element used to plate other metals and electroplating factories are still considered to be the most important industries which pollute the environment to this metal. This paper describes a study conducted to determine the efficiency of reverse-osmosis (RO) as a membrane technique for removal of Cr from wastewater samples synthetically prepared to be similar to electroplating effluents. Methods: The RO unit used in this study was a spiral wound module of 2521 TE made by a Korean CSM company. Synthetic wastewater samples containing Cr ions at various concentrations of 1 to 20 mg/L were prepared and subjected to treatment by RO, and quantitative analysis had been accomplished by a colorimetric method. Evaluation of optimized conditions of treatment had also been carried out by determining the effects of changing operating pressure, temperature and pHS of samples. Results: Optimum conditions of Cr-treatment by RO in 10 g/L initial Cr concentration were determined to be in the pH range of 6 to 7 and in temperature of about 25ºC at an applied pressure of 200 psi. Conclusion: Considering the efficiency of Cr removal which was as high as 99% at the optimized conditions it could be concluded that RO membrane process may be selected and developed as an effective alternative for treatment of metal-contaminated effluents of electroplating and similar industries.